Given
x + y x − y = = 3 1
What is the value of x y ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The line y = 3 − 1 = 1 is wrong. Please correct it.
Log in to reply
i typed very quickly, so made the mistake. anyway thanks i have changed that.
Let x+y=3 be equation 1.
Let x-y=1 be equation 2.
Subtract them :
x+y=3
x-y=1
2y=2
And solve:
2y=2
y=1
Now substitute y=1 into either equation 1 or 2 to solve for x.
x+y=3
x+1=3
x=3-1
x=2
Now use the values to find xy:
xy
=2(1)
=2
x + y = 3 ..................(1)
x − y = 1 ...................(2)
From equation (1)
x + y = 3
⇒ x = 3 − y ....................(3)
Substitute x = 3 − y is equation (2)
3 − y − y = 1
⇒ y = 1
Substitute the value of y in equation (3)
x = 3 − 1
⇒ x = 2
Therefore x y = 2 ;[ 2 × 1 ]
Given x + y = 3 and x − y = 1
⇒ ( x + y ) + ( x − y ) = 3 + 1 = 4
2 x = 4 ⇒ x = 4 ÷ 2 = 2
We know that x = 2 . Replacing x = 2 in:
x + y = 3 ⇒ y = 1 , and x − y = 1 ⇒ y = 1 . Therefore, y = 1
So the answer of x y = 2 × 1 = 2
\[ \begin { align } \begin { cases } x + y = 3 \\ x - y = 1 \end { cases } \\ 2x = 4 \\ x = 2 \\ \begin { cases } 2 + y = 3 \\ 2 - y = 1 \end { cases } \\ y = 1 \\ \therefore xy = 2 \end { align } \].
X plus y equals three. That means that x has to be 0, 1, 2, or 3. But X can't be 0 or 3 because the x minus y would not equal 1. So the answer would be 2 and 1. And 2 times 1 equals 2
Let x+y=3 be equation 1.
Let x-y=1 be equation 2.
Subtract them :
x+y=3
x-y=1
2y=2
And solve:
2y=2
y=1
Now substitute y=1 into either equation 1 or 2 to solve for x.
x+y=3
x+1=3
x=3-1
x=2
Now use the values to find xy:
xy
=2(1)
=2
Having sum and difference of two numbers you can simply obtain the two numbers this way: ( x + y ) + ( x − y ) = 2 x ( x + y ) − ( x − y ) = 2 y
so we have:
x = ( 3 + 1 ) / 2 = 2 y = ( 3 − 1 ) / 2 = 1
Problem Loading...
Note Loading...
Set Loading...
x + y = 3 ........................[1]
x − y = 1 .........................[2]
from [1]+[2],we get, 2 x = 4 , or, x = 2
so, y = 3 − 2 = 1
now, x y = 2 × 1 = 2